Employee Productivity in Banking: The Role of Transformational Leadership and Work-Life Balance with Work Motivation as a Mediator (McClelland Theory) - Indra Febri Wicaksono; Djoko Soelistya; Eva Desembrianita (Universitas Mercu Buana, 2026)
Objectives: This study aims to examine the effects of transformational leadership and work-life balance on employee productivity, with work motivation serving AS a mediating variable based on McClelland’s Theory of Needs. The study seeks to explain how leadership practices and employee well-being contribute to productivity enhancement in the banking sector.Methodology: This research employed a quantitative explanatory approach. Data were collected through structured questionnaires distributed to employees of Bank Syariah Indonesia (BSI) in the Gresik Region. The population consisted of 250 employees, and a sample of 154 respondents was selected using simple random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement and structural models, including direct and indirect effects among variablesFinding: The findings suggest that transformational management definitely and drastically impacts employees. productiveness (β = 0.30; p < zero.001) and work motivation (β = 0.45; p < zero.001). work-lifestyles stability also positively and significantly affects worker productiveness (β = zero.25; p = zero.003) and work motivation (β = 0.35; p < 0.001). moreover, work motivation notably affects employee productiveness (β = zero.forty; p < 0.001). The mediation analysis shows that paintings motivation in part mediates the relationships among transformational management and worker productiveness (β = zero.18; p < zero.001), in addition to among work-life stability and worker productivity (β = zero.14; p = zero.001). The structural model explains sixty five% of the variance in paintings motivation and seventy two% of the variance in worker productivity.Conclusion: This research finds that Employee productivity in the banking sector is affected by both organizational elements and motivational aspects. The findings extend McClelland’s Theory by demonstrating that work motivation acts as a crucial link between transformational leadership and work-life balance to employee productivity. Therefore, banking organizations should strengthen transformative leadership practices and paintings-lifestyles balance policies to enhance worker motivation and achieve sustainable productivity improvements.